Peningkatan Hasil Belajar Siswa Pada Pembelajaran Geografi Melalui Model Discovery Learning - Pratiwi, Pratiwi; Zhiddiq, Sulaiman; Umar, Ramli; Saputro, Alief (UNIVERSITAS NEGERI MAKASSAR, 2021)
This study aims to: 1) find out how the picture of learning outcomes of students by using the Discovery Learning learning model in class X SMA Negeri 3 Luwu Utara. 2) find out the increase in geography learning outcomes by using the Discovery Learning learning model in class X SMA Negeri 3 Luwu Utara. The target in this study were students of class X IIS 2 in SMA Negeri 3 North Luwu, totaling 30 students. This type of research is Classroom Action Research (PTK). Consists of 2 cycles where each cycle consists of three meetings. The first and second meetings are material giving and the third meeting is the evaluation of the end of the cycle. The results of this study indicate 1) The average learning outcomes of students before using the discovery learning model is 40.67. Then increase after the application of discovery learning models in the first cycle of 63.267 included in the medium category, and in the second cycle of 75.33 also included in the medium category with a percentage increase of 13.79%. 2) The results of observations of students' activities in the teaching and learning process also increased, in the first cycle of the first meeting of 60.14% and then an increase in the second meeting of 68.88%. In the second cycle the first meeting amounted to 70.83% and experienced a change in the second meeting amounted to 78.47% included in the category of